2007
DOI: 10.1002/tie.20142
|View full text |Cite
|
Sign up to set email alerts
|

Regulation and performance of Islamic banking in Bangladesh

Abstract: This article examines current legal and regulatory issues of Islamic banking in Bangladesh. The most important issue in this context is the lack of a well‐defined regulatory and supervisory framework for Islamic banks for their effective functioning in line with the tenets of Shariah. Other major issues come from the absence of an interbank Islamic money market, following the same policy and guidelines for Islamic and conventional banking by the Bangladesh Bank, presence of a discriminatory legal reserve requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
93
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(97 citation statements)
references
References 7 publications
3
93
1
Order By: Relevance
“…Additionally, Ahmad and Hassan (2007) found that a well-defined supervisory framework and regulatory regime plays an influential role in the effective functioning of Islamic banking. At the minimum level, a conventional bank that wishes to convert into Islamic form needs to consider if a basic regulatory and accounting framework has been established in the nation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Additionally, Ahmad and Hassan (2007) found that a well-defined supervisory framework and regulatory regime plays an influential role in the effective functioning of Islamic banking. At the minimum level, a conventional bank that wishes to convert into Islamic form needs to consider if a basic regulatory and accounting framework has been established in the nation.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, external intervention in organisational transformation may interact with internal environment factors, and weaken or reinforce its impact on transformation. Although some studies have examined the impact of regulation on performance in the Islamic banking sector (Ahmad and Hassan, 2007;Tsikouras, 2009;Zaher and Hassan, 2001), there is relatively little knowledge regarding the combined effect of external and internal environment factors on organisational transformation, with an emphasis on converting conventional retail banking into Islamic lines. Therefore, this paper proposes hypotheses on the moderating effect of banking law and regulation on the relationship between successful transformation and determining variables, namely competent human resources, relevant experiences, willingness, and Islamic capital market.…”
Section: Supportive Banking Law and Regulationmentioning
confidence: 99%
See 2 more Smart Citations
“…For the past few decades, Islamic banking had grown very well due to the increasing demand of better service quality and the need to improve. Customer have knowledge and they know what they are capable of, thus pushed Islamic banking to flourish and overcome conventional banking (Ahmad and Hassan, 2007). With the growth rate of 25-20 % annually, Islamic banking shows great potential to surpass conventional † Sharia is the religious law governing the members of the Islamic faith.…”
Section: Service Qualitymentioning
confidence: 99%